A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil - Lourenço, Ana Carolina C.; Zina, Juliana; Catroli, Gaucilene F.; Kasahara, Sanae; Faivovich, Julian; Haddad, Célio F. B. (Zootaxa, 2016)
We describe a new species of the Scinax catharinae group from coastal forest in the State of São Paulo, Brazil. We also describe the karyotype and the advertisement call of the new species, which is composed by a multipulsed note. The chromosome morphology of the new species shows the nucleolar organizer region (NOR) on Pair 6, a putative synapomorphy previously inferred for the S. catharinae clade. We report, for the first time, the presence of mental glands in a species of the genus Scinax. Additionally, we provide a brief discussion about the occurrence of glandular tissue on the mental and inguinal regions of the species of the S. catharinae clade.